Inhibition of secondary metabolite extract of Streptomyces sp. on Plasmodium falciparum in vitro: A study of soil sediment of Papua's Hamadi mangrove forest - Sandy, Semuel; Sasto, Iman Harisma Saleh (JKKI : Jurnal Kedokteran dan Kesehatan Indonesia, 2020)
Background: Reports about the resistance of antimalarial drugs demand exploration and development of new drugs. Indonesia's vast maritime area and abundance of mangrove forests have the potential for the development and discovery of active anti-cancer substances, antibiotics and antiplasmodial. Studies on the potential of new drugs from this sector are still limited. Objective: The purpose of this study was to see the potential of Actinomycetes genus Streptomyces sp. as an antiplasmodial in the Hamadi Coast of Papua. Methods: Retrieval of mangrove soil sediments to isolate Streptomyces was located in the Hamadi-Jayapura mangrove forest. Selective isolation was conducted by SCA (Starch Casein Agar) selective media. Identification of Streptomyces sp was examined microscopically through observation of colony morphology and gram staining. The results of isolation of Streptomyces were then fermented on FM3 media until finally secondary metabolite extract of Streptomyces was obtained. The secondary metabolite extract of Streptomyces was tested for its inhibition on the development of Plasmodium falciparum. Result: Analysis of inhibition of the secondary metabolite extract of Streptomyces sp on the development of Plasmodium falciparum showed good results because the extract of Streptomyces sp with a concentration of 100 µg/mL could suppress average growth values of Plasmodium falciparum to only 0.66% with an average inhibitory value of 95.20%. This value followed levels of extract concentration by the lowest concentration of 0.01 µg/mL, the average value of Plasmodium falciparum growth which increased to 10.89% with an average inhibition value of 20.83%. IC50 analysis of Plasmodium falciparum in culture for 48 hours was 0.12 µg/mL, and this value was very good because a test of substance has very good inhibitory activity when the IC50 value is = 10 µg/mL. Conclusion: Streptomyces’ secondary metabolite extract from mangrove sediments showed a very good ability to inhibit the growth of Plasmodium falciparum so that it could have potential as a source of antiplasmodial.